Eh-Sayyeh, Jordanien: Die Arbeiten des Jahres 2014 - Bartl, Karin; Kafafi, Zeidan (e-Forschungsberichte des DAI, 2023)
The Neolithic site of eh-Sayyeh located ca. 25 km northeast of Amman is a unique settlement which allows the study of various questions on the transition from the Early to the Late Neolithic period at the end of the 8th / beginning of the 7th millennium BC. This includes, among other issues, the aspect of settlement size in the different Neolithic phases. So far, the excavations exposed some extraordinary architectural forms, of which parallels are only known from sites in the eastern desert at a distance of ca. 200 km. These results raise questions of the nature and extent of cultural contacts between the two regions.